Enhancing Mathematical Thinking Skills in Elementary Fraction Learning through the RADEC Model: A Systematic Literature Review - Susanti, Eti; Sopandi, Wahyu; Supriadi, Supriadi (Journal of Innovation and Research in Primary Education, 2025)
Mathematical thinking skills represent fundamental cognitive capacities essential for fraction concept mastery in elementary education, yet traditional instructional approaches consistently fail to address persistent learning difficulties. The RADEC (Read-Answer-Discuss-Explain-Create) model offers a promising framework for enhancing mathematical thinking through systematic collaborative learning processes. This systematic literature review examined the effectiveness of RADEC implementation in developing mathematical thinking skills, particularly for fractional concept instruction in elementary settings. A comprehensive search across multiple databases including Google Scholar, JSTOR, ERIC, and PubMed identified 946 potentially relevant studies published between 2019-2023. Through systematic screening applying rigorous inclusion and exclusion criteria, 21 high-quality studies were selected for analysis using thematic synthesis methodology. The results demonstrate that RADEC implementation significantly improves conceptual understanding, critical thinking skills, mathematical communication abilities, and higher-order thinking competencies compared to conventional instructional approaches. While no studies specifically examined RADEC with fractional content, the model's theoretical principles align closely with established best practices for fraction instruction, including collaborative discourse, concrete representations, and conceptual understanding development. Implementation challenges include variations in students' reading abilities, teacher preparedness requirements, and instructional resource limitations. The findings reveal a critical research gap regarding direct empirical testing of RADEC effectiveness with fractional content. This review contributes the first comprehensive synthesis linking RADEC principles with mathematical thinking development and fraction instruction, providing theoretical foundation for future empirical research while highlighting practical implementation requirements for educational practitioners.